Pengelolaan Perdagangan Pakaian Bekas: Studi antara Indonesia dan Thailand untuk Menghentikan Penyelundupan Pakaian Bekas - Vanessa Babyliany; Ninne Zahara Silviani; Windi Afdal (Universitas Muhammadiyah Ponorogo, 2026)
This study discusses legal issues surrounding the management of secondhand clothing trade (thrifting) in the context of preventing smuggling through a comparative study between Indonesia and Thailand. The main issues examined are the differences in regulatory approaches between the two countries and their implications for the effectiveness of law enforcement and consumer protection. The research method used is normative juridical with a legislative approach and a comparative law approach, analyzing national regulations and international legal instruments, including the Basel Convention (1989). The results show that Indonesia implements a restrictive policy on the import of used clothing, but faces obstacles in terms of supervision and the legal culture of society, so that smuggling practices still continue. In contrast, Thailand implements a more adaptive licensing and hygiene supervision mechanism, thereby creating harmony between the legal structure, legal substance, and legal culture. Normatively, this study concludes that the management of the used clothing trade requires a balance between legal certainty and effective supervision, as well as a regulatory approach that is in line with the principles of sustainability and the circular economy.